Penggunaan Blok Dienes untuk Meningkatkan Hasil Belajar Konsep Penjumlahan Bilangan Cacah pada Siswa Sekolah Dasar - Mozes Yustus Legi (Peneliti.net, 2021)
The purpose of this study was to describe how the use of concrete objects that can improve the mastery of the concept of summing counted numbers in grade I SD GMIM XIV Manado. This study uses a classroom action research method, by carrying out 2 cycles. The results of the study are as follows. The use of dienes block concrete objects carried out in this study proved to be effective, namely it could improve the mastery of the concept of summing counted numbers in grade I students of SD GMIM XIV Manado. The use of dienes block concrete objects is used to teach the concept of summing whole numbers through the enactive stage, the iconic stage, and the symbolic stage. The use of concrete objects in mathematics learning can create a pleasant learning atmosphere. The use of block dienes makes it easier for students to understand the concept of adding whole numbers